Therapeutic choices and care of minors: a recent story - Alfano, Linda; Bonsignore, Alessandro; Ciliberti, Rosagemma (Medicina Historica, 2019)
The profound social, ethical and juridical transformations that have invested the condition of childhood have also affected the consideration of the existential interests of the minor in the care relationship and his role in the adoption of the therapeutic choices that concern him. If the history of children’s rights is recent, that of children’s rights in the health field is still at the outset. The legal status of the minor in the medical field expresses all the complexity of a status that, for a long time, has been subject to profound reconsiderations and which concerns various and different stages of growth and the formation of his personality. The participation of the child is an important factor to condition the therapeutic path and improve the curative results. However, the participation of the minor in his/her health path still has obstacles and shortcomings. The promotion of a specific communicative competence of health professionals can represent an important factor capable of contributing to the growing autonomy of the child and positively influencing the therapeutic path.